2013
DOI: 10.1186/1743-8977-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative absorption, distribution, and excretion of titanium dioxide and zinc oxide nanoparticles after repeated oral administration

Abstract: BackgroundThe in vivo kinetics of nanoparticles is an essential to understand the hazard of nanoparticles. Here, the absorption, distribution, and excretion patterns of titanium dioxide (TiO2) and zinc oxide (ZnO) nanoparticles following oral administration were evaluated.MethodsNanoparticles were orally administered to rats for 13 weeks (7 days/week). Samples of blood, tissues (liver, kidneys, spleen, and brain), urine, and feces were obtained at necropsy. The level of Ti or Zn in each sample was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
209
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(239 citation statements)
references
References 35 publications
11
209
1
10
Order By: Relevance
“…For example, a study where TiO 2 nanoparticles (mixture of anatase and rutile at 21 nm) were repeatedly administered (260-1041 mg/ kg) to rats did not report any significant toxicity or TiO 2 accumulation in tissues or urine, but reported high concentrations of titanium dioxide in feces, suggesting that the TiO 2 nanoparticles were mostly eliminated. 65 The observed contradictions between different animal studies on the accumulation and toxicity of TiO 2 nanoparticles may arise for a number of reasons. Firstly, there are differences in the oral dose, crystal form, particle size, aggregation state, and surface characteristics of the nanoparticles used.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study where TiO 2 nanoparticles (mixture of anatase and rutile at 21 nm) were repeatedly administered (260-1041 mg/ kg) to rats did not report any significant toxicity or TiO 2 accumulation in tissues or urine, but reported high concentrations of titanium dioxide in feces, suggesting that the TiO 2 nanoparticles were mostly eliminated. 65 The observed contradictions between different animal studies on the accumulation and toxicity of TiO 2 nanoparticles may arise for a number of reasons. Firstly, there are differences in the oral dose, crystal form, particle size, aggregation state, and surface characteristics of the nanoparticles used.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…75 However, this result is in contrast to another animal study where a mixture of anatase and rutile forms of TiO 2 nanoparticles did not cause significant toxicity in rats. 65 One possible reason is that cells were exposed to pristine-TiO 2 nanoparticles in the serum-free media used in the cell culture study, but they were exposed to coated TiO 2 nanoparticles in the animal studies (because the nanoparticle surfaces adsorb substances from the surrounding GIT fluids). This discrepancy may therefore be due to differences in the biological fate and toxicity of TiO 2 nanoparticles with different interfacial properties.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…In some studies it is debated whether TiO 2 NPs are absorbed after oral exposure, as an increase in organ levels is not always found (Cho et al, 2013). Other studies, however, suggest that there is absorption based on the dose-dependent increase of Ti in various organs in oral studies with NPs and visual detection of (TiO 2 ) particles in these organs (Tassinari et al, 2014).…”
Section: Toxicokinetics Study For Tio 2 Npsmentioning
confidence: 99%
“…Indeed, Banasaz et al, [14], found most pronounced effects of gender in the morphometric parameters of the upper part of the small intestine, identifying testosterone as a key factor in proliferative effect [14]. The gender-specific differences in NP toxicity has been already recorded; in male rats, spherical 26 nm TiO 2 NPs -orally administered by gastric gavage for 90 dayssignificantly increased the level of Ti in blood to approximately 1.25-fold of the background levels in nonexposed rats; no significant increased level was recorded in female rats [7]. Moreover, Tassinari et al, [1] found sex-specific patterns of effects in rats treated for five days with TiO 2 anatase NPs, since adrenal cortex and spleen were affected in females only, whereas T3 serum levels were altered in male rats only.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of TiO 2 can be different according to the exposure routes and there is little knowledge on how the kinetic relates to physicochemical characteristics such as size [7].…”
Section: Introductionmentioning
confidence: 99%